Morphometry and Topographic Wetness Index Analysis for flood inundation mapping in Mata Allo watershed (South Sulawesi, Indonesia); Rezumat. Analiza morfometriei şi a indicelui topografic de umiditate pentru cartarea inundaţiilor în bazinul Mata Allo (sudul insulei Sulawesi, Indonesia) - Uca, Uca; Lamada, Mustari; Nyompa, Sukri; Haris, Nurul Afdal (University of Craiova, Faculty of Social Sciences, Department of Geography, 2022)
Lorem Along with climate change, natural disasters will occur more frequently such as floods. Floods that occur in watersheds which include various human activities, such as Mata Allo (Indonesia) will especially cause a large enough impact. The elongated shape o f the watershed has a slow response to peak discharge and time lag. The Mata Allo watershed is dominated by slopes above 25→45 (65) and agricultural land use which accounts for 53 of the area, which has an obvious impact on the amount of runoff and ero sion that occurs. The eroded soil will be carried away by surface runoff and deposited in the plains between mountains and river floodplains. Based on the results of the study, the Topographic Wetness Index (TWI) map indicates that the part between the mou ntains and the floodplain around the Mata Allo river had a high TWI value. A high TWI value indicates a high vulnerability to anticipate flooding in the event of overflowing from the Mata Allo River. River morphometry, land use, and hydrological behavior i n a watershed are closely related to the TWI value in the Mata Allo watershed. © 2022 The Author(s).